Psychometric Properties of Dispositional Hope Scale for Brazilian Sport Context. (18th May 2018) - Moreira, Caio Rosas; Nascimento-Junior, José Roberto Andrade; Codonhato, Renan; Fiorese, Lenamar
Abstract: This study investigated the psychometric properties of the Dispositional Hope Scale (DHS) for the Brazilian sport context. The sample for construct validity consisted of 474 athletes; internal validity was assessed with 101 athletes; and external validity was tested in 81 athletes, from which, were 55 had further participated in the temporal stability assessment. Data analysis was conducted through the following tests: Cronbach's alpha, Composite Reliability (CR), Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Spearman Correlation Coefficient and intraclass correlation. Results had shown that the DHS presents satisfactory internal consistency (.79 ≤ α ≤ .83; .58 ≤ r ≤ .75). The EFA model revealed a two-factor solution to be the most adequate, while CFA confirmed such model (χ 2 = 59.88; p < .001; χ 2 / df = 3.15; CFI = .90; AGFI = .94; TLI = .90; RMSEA = .07 CI [.05, .08]). The hope dimensions were positively correlated with Self-esteem ( r > .50). Temporal stability was achieved (ICC > .70). It was concluded that the DHS is a valid measure for the assessment of hope in Brazilian sports context; this instrument has potential practical applications for professionals working with Sport Psychology.